DIAGNOSIS DAN PENATALAKSANAAN KUSTA - hendra T (CV. Jasa Sukses Abadi, 2022)
Leprosy or Morbus Hansen or lepra is a chronic infectious disease caused by the bacillus Mycobacterium leprae. Leprosy attacks the peripheral nerves, skin, and other body tissues except the central nervous system. Mycobacterium leprae reproduces slowly and the average disease incubation period is 5 years. Symptoms can occur within 1 year but can also last for 20 years or even more. This disease can be cured with multidrug therapy. Kusta is likely transmitted by droplets, from the nose and mouth, during close and frequent contact with untreated cases. Diagnosis of leprosy is based on clinical, bacterioscopic, histopathological, and serological features. Of the three, clinical diagnosis is the most important and the simplest. Determination of the type of leprosy needs to be done in order to determine the appropriate therapy. In several provinces in Indonesia, the prevalence of Leprosy is still above 1 per 10,000 population where this figure cannot be declared free of Morbus Hansen and occurs in 10 provinces in Indonesia. Kusta sufferers not only suffer because of their illness but also suffer psychological impacts because people think that Leprosy is a hereditary disease. Based on the description, it is necessary to explore and know about the definition, etiology, pathogenesis, clinical manifestations, investigations, complications, management, and prognosis of Leprosy.